Vestibular Schwannoma Presenting as Oral Dysgeusia: An Easily Missed Diagnosis - Emma Brown; Konrad Staines (Case Reports in Dentistry)
We present a case of a fifty-year-old male patient who was referred to the Oral Medicine Department with a complaint of a salty taste. History taking subsequently revealed that the patient was also experiencing intermittent numbness of his left lower lip, tinnitus, and a feeling of fullness in the left ear. Magnetic resonance imaging was performed which revealed a large vestibular schwannoma affecting the left vestibulocochlear nerve, which was treated surgically. This case shows the importance of taking a detailed history in a patient presenting with an initial complaint of oral dysgeusia. It also highlights the possibility of significant underlying pathology, presenting with initial low level, nonspecific complaints such as an altered taste, and the rationale for imaging patients who report unilateral facial hypoesthesia.